The Aurora kinase inhibitor AT9283 inhibits Burkitt lymphoma growth by regulating Warburg effect - Jiang, Kaiming; Bai, Lihong; Wang, Canfei; Xiao, Xiang; Cheng, Zhao; Peng, Hongling; Liu, Sufang (PeerJ, 2023)
Objective To investigate the effect of the kinase inhibitor AT9283 on Burkitt lymphoma (BL) cells and elucidate the underlying mechanisms. Methods The effect of AT9283 on the proliferation of BL cell lines was tested using the MTT assay. Apoptosis and cell cycle were measured by flow cytometry. The proteins associated with the cell cycle, apoptosis, and the Warburg effect were detected using Western blotting. Alterations in glycolytic metabolism in terms of glucose intake and lactate concentrations were determined by glucose and lactate assays. Results The current study utilized the GEPIA, the Human Protein Atlas (HAP) database and immunohistochemistry to conduct analyses, which revealed a high expression of Aurora kinases and Warburg effect-related proteins in malignant B-cell lymphoma tissues. AT9283 significantly inhibited the cell proliferation of BL cells and induced G2/M arrest. Additionally, AT9283 induced apoptosis in BL cells and reversed the Warburg effect by increasing glucose uptake and reducing lactate production. Moreover, the protein expression of hexokinase 2, pyruvate kinase M2, and lactate dehydrogenase A was significantly suppressed by AT9283, possibly through the inhibition of c-Myc and HIF-1α protein expression. Conclusion The reversal of the Warburg effect in BL cells and the subsequent inhibition of cell proliferation and induction of apoptosis were observed by targeting Aurora A and Aurora B with AT9283. This finding may present new therapeutic options and targets for BL.
Keywords: Aurora kinase; AT9283; Burkitt lymphoma; Warburg effect; c-MYC; HIF